Inhibitory activity of Escherichia coli by type of teas and its liquors - Dadan Rohdiana; Dede Zainal Arief; Arista Budiman (Jurnal Penelitian Teh dan Kina, 2013)
Study of analysis polyphenol content on tea, liquor, and its activity as antibacterial on Escherichia coli has been done conducted in Laboratory of Research, Department of Food Technology, Pasundan University, and Laboratory of Chemistry, Department of Chemistry, Faculty of Mathematic and Natural Science, Padjadjaran University. The result of this research showed that green tea sample has the highest polyphenol content, i.e. 23,18% followed orthodox and CTC (crushing tearing curling) black tea samples i.e. 14,23%Â  and 13,93% respectively. Activity of inhibitory on E. coli showed that ratio tea and water 2 : 50 w/v has the best inhibition i.e. 117,71 mm2.